The effect body mass index on varicocele - Mohammad, Ehab Jasim; Abbas, Kanaan Mahdi; Abd, Ali Hussein; Abdulrazaq, Alaa Abdulqader (International Surgery Journal, 2018)
Background: Varicocele, is the most common abnormal finding among men presenting with infertility, yet controversy exist regarding their etiology. Anecdotal experience suggests that varicoceles are more prevalent in lean men, supporting the “nutcracker” effect of the superior mesenteric artery compressing the left renal vein over the aorta. The aim of this study was to determine the association between Body Mass Index (BMI) and occurrence of varicocele. Methods: A total of 100 males with varicocele attending the urological outpatient clinic were evaluated from their physical screening examinations. All subjects underwent history taking and physical examinations to evaluate for the presence and severity of varicocele, height, weight, and BMI, those compared with 100 men without varicocele (control group) were selected randomly from general population. Results: The mean BMI of the 100 patients with varicocele was 26.1620 while that of the control group was 29.7330 (P= 0.0001) which is clinically significant. Varicocele grade decreased with increasing BMI category (P= 0.0001). Conclusions: The results of this study indicate that there is a decreasing incidence of varicocele and varicocele grade with increasing BMI, Supporting the possibility that obesity results in a decreased nutcracker effect in which the adipose tissue prevents compression of the renal vein.